Legal and Policy Coherence in Nepal’s Hydropower Sector: A Constitutional and Institutional Analysis - Ojha, Krishna Prasad (SS Multidisciplinary Research Journal, 2025)
This qualitative study critically analyzes the coherence and effectiveness of Nepal’s constitutional, legal, and policy frameworks governing hydropower development, emphasizing sustainability, social equity, and institutional accountability. Despite possessing an estimated 83,000 MW of theoretical hydropower potential, Nepal has utilized less than five percent due to fragmented governance, outdated legislation, and weak policy coordination. Employing a doctrinal legal research approach, the study examines constitutional mandates, statutory instruments, sectoral policies, and international environmental commitments to assess their alignment with national development objectives. The findings reveal a significant gap between constitutional principles of equitable resource distribution and the practical enforcement of environmental and social safeguards. Overlapping institutional mandates, insufficient coordination among agencies, limited public participation, and inadequate grievance mechanisms have undermined effective governance and justice for affected communities. Comparative insights from Bhutan and India demonstrate that coherent legal integration, transparent regulation, and participatory governance substantially enhance hydropower sustainability and social legitimacy. The study concludes that Nepal urgently requires comprehensive legal harmonization, particularly through the formulation of an integrated Hydropower Act and the strengthening of environmental compliance and benefit sharing frameworks. Such reforms are essential to align economic growth with ecological integrity and social justice. Ultimately, the study aims to identify structural and institutional reforms necessary to transform hydropower into a cornerstone of Nepal’s sustainable energy transition and inclusive national development.